Sex-specific Acute Cerebrovascular Response to Photothrombotic Stroke in Mice Requires Rho-kinase - Raman-Nair, Joanna (Université d'Ottawa / University of Ottawa, 2022)
With high energy consumption and a low capacity for energy storage, the brain is highly dependent on a continuous supply of oxygen and nutrients from the bloodstream. Ischemic stroke, caused by the occlusion of a cerebral blood vessel, compromises cerebral blood flow (CBF), resulting in detrimental effects on brain homeostasis, vascular function, and neuronal health. Sex differences in ischemic stroke are known, with women having lower rates of stroke due to a protective role of estrogens on vascular health, and more severe strokes following reduced estrogen production after menopause. Rho-associated protein kinase (ROCK), an important regulator of vascular tone, also regulates vascular function in a sex-specific manner, and its deletion is neuroprotective following ischemic stroke. The current study explores the overlapping roles of ROCK and endogenous hormone influence on the acute CBF response to a photothrombotic (PT) model of ischemic stroke in mice. CBF was measured following stroke in the somatosensory cortex in mice with a heterozygous deletion of the ROCK2 isoform (ROCK2+/-) and in wild-type (WT) littermates. To remove endogenous hormones, male mice were gonadectomized (Gdx) and female mice were ovariectomized (Ovx), and control animals received a sham surgery (“intact”) prior to stroke induction. Intact WT males showed a delayed CBF drop compared to intact WT females, where peak drop in CBF wasn’t observed until 48 hours following stroke. Gonadectomy in males did not alter this response, however ovariectomy in females produced a “male-like” response. ROCK2+/- males also showed such phenotypic response, and Gdx did not alter this response, suggesting ROCK2 deletion or endogenous male hormones do not alter CBF response in males in this stroke model. Alternatively, intact ROCK2+/- females showed a striking difference in CBF values compared to intact WT females, where they displayed higher CBF values immediately post-stroke and also showed a peak drop in CBF at 48 hours post-stroke. Ovx did not change the CBF response in ROCK2+/- females. Overall, there is a marked difference between males and females in their acute CBF responses to PT stroke, which appears to be mediated by endogenous female sex hormones and ROCK2. All groups except for intact WT females show a delayed drop in CBF values, reaching a maximal drop in CBF at 48 hours following stroke induction. This may be due to hyperreactivity of female platelets and upregulation of RhoA/ROCK signaling in female platelets. Further research is required to confirm this speculation. This study reveals important sex-differences and the involvement of ROCK2 in acute CBF responses to PT stroke in mice.
Keywords: ischemic stroke; rho-kinase; ROCK; estrogen; sex hormones; cerebral blood flow